2006
DOI: 10.1002/art.21718
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in waist‐high warm water decreases pain and improves health‐related quality of life and strength in the lower extremities in women with fibromyalgia

Abstract: Objective. To evaluate the short-and long-term efficacy of exercise therapy in a warm, waist-high pool in women with fibromyalgia. Methods. Thirty-four women (mean ؎ SD tender points 17 ؎ 1) were randomly assigned to either an exercise group (n ‫؍‬ 17) to perform 3 weekly sessions of training including aerobic, proprioceptive, and strengthening exercises during 12 weeks, or to a control group (n ‫؍‬ 17). Maximal unilateral isokinetic strength was measured in the knee extensors and flexors in concentric and ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 42 publications
6
105
0
12
Order By: Relevance
“…This represents a large effect (MLSI effect size, R 2 = 0.26), when patients were evaluated with eyes closed. These improvements are similar to those reported previously 35 (for example, Rees et al 25 demonstrated improvements in MLSI of 27.5% and Gusi et al 35 and Gusi et al 32 demonstrated improvements in balance of 29% and 36%, respectively, with short-term WBV training). ANCOVA, analysis of covariance; SI, stability index; AP, anteroposterior; MD, mean deflection; ML, medial-lateral; effect size, > 0.01 small; > 0.06 medium; > 0.14 large.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This represents a large effect (MLSI effect size, R 2 = 0.26), when patients were evaluated with eyes closed. These improvements are similar to those reported previously 35 (for example, Rees et al 25 demonstrated improvements in MLSI of 27.5% and Gusi et al 35 and Gusi et al 32 demonstrated improvements in balance of 29% and 36%, respectively, with short-term WBV training). ANCOVA, analysis of covariance; SI, stability index; AP, anteroposterior; MD, mean deflection; ML, medial-lateral; effect size, > 0.01 small; > 0.06 medium; > 0.14 large.…”
Section: Discussionsupporting
confidence: 89%
“…For example, patients with FM have increased frequency of falls 17 and may suffer premature bone loss. 37 WBV can be used to address both of these important clinical problems 35 in addition to improving strength and fitness in FM.…”
Section: Sañ Udo Et Almentioning
confidence: 99%
“…However, Hooten et al (3) revealed equal reductions in pain severity following either strengthening or aerobic exercise training. Aerobic fitness has also been reported to be inversely associated with overall FM severity (28), and most exercise intervention programs in FM patients involve both aerobic and muscle strengthening exercises (29)(30)(31)(32). Therefore, these exploratory results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 98%
“…Some techniques and resources need more studies to prove its effectiveness in the treatment of TMD 20 . Gusi et al 21 evaluated short-term and long-term effectiveness of exercise therapy in a heated swimming pool in women with fibromyalgia. They observed that the quality of life was improved in 93% and pain was reduced by 29% compared to the control during training and even after the therapy interruption.…”
Section: Discussionmentioning
confidence: 99%